Keikhlasan Survivor Bencana Tsunami dan Gempa Aceh - Nashori, Fuad (Unisia, 2009)
This article aims to elaborating the results of study on the consciousness of the survivors of the earthquake and tsunami disasters in Aceh. The study, using interview and observa- tion methods, reveals that the survivors have some such consciousnesses as: spiritual conciousness; psychological readiness; self reliance to shoulder any life burden; God forgiveness seeking; life meaning seeking; positive thinking; regretting of the past; sur- rendering to God and seeking God help. The study also shows some factors affecting the consciousness of the survivors, such as: faiths, knowledges, experiences, and family supports. Keywords: Consciousness, disasters, survivors